Model of Corporate Criminal Liability in Preventing Corporate Recidivism in Money Laundering Offenses - Fadilah, Fatma Putri; Prasetyo, Handoyo (Universitas Semarang, 2025)
This study analyzes corporate criminal liability in money laundering cases involving PT Duta Palma Group through the lens of deterrence theory and examines strategies to optimize corporate liability to prevent repeat corporate offending. The research is motivated by the inadequate application of corporate criminal sanctions in the conviction of Surya Darmadi, the owner of PT Duta Palma Group, which failed to prevent subsequent money laundering offenses committed by Cheryl Darmadi involving cross-border fund transfers to Hong Kong and her escape to Singapore. A normative juridical method was employed, utilizing statutory, conceptual, comparative, and case approaches. The novelty of this study lies in its integration of Jeremy Bentham’s deterrence theory with a comparative analysis of the French legal framework to develop a more effective model for corporate criminal liability. The findings indicate that the court's decision against Surya Darmadi lacked a sufficient deterrent effect because the sanctions imposed were not proportional to the financial and social harms caused. This study proposes a reformulated model for enhancing corporate criminal liability based on proportional sanctions, strengthened deterrence mechanisms, and the adoption of relevant features from the French legal system. Such a framework is expected to reduce the likelihood of corporate recidivism and promote more effective enforcement in money laundering cases.